Mountain pine beetle infestation impacts: modeling water and energy budgets at the hill‐slope scale. Issue 1 (15th December 2011) - Mikkelson, K. M.; Maxwell, R. M.; Ferguson, I.; Stednick, J. D.; McCray, J. E.; Sharp, J. O.
ABSTRACT The mountain pine beetle (MPB) epidemic in western North America is generating growing concern associated with aesthetics, ecology, and forest and water resources. Given the substantial acreage of prematurely dying forests within Colorado and Wyoming ( two million acres in 2008), MPB infestations have the potential to significantly alter forest canopy, impacting several aspects of the local water and land‐energy cycle. Hydrologic processes that may be influenced include canopy interception of precipitation and radiation, snow accumulation, melt and sublimation, soil infiltration and evapotranspiration. To investigate the changing hydrologic and energy regimes associated with MPB infestations, we used an integrated hydrologic model coupled with a land surface model to incorporate physical processes related to energy at the land surface. This platform was used to model hillslope‐scale hydrology and land‐energy changes throughout the phases of MPB infestation through modification of the physical parameterisation that accounts for alteration of stomatal resistance and leaf area indices. Our results demonstrate that MPB infested watersheds will experience a decrease in evapotranspiration, an increase in snow accumulation accompanied by earlier and faster snowmelt and associated increases in runoff volume and timing. Impacts are similar to those projected under climate change, yet with a systematically higher snowpack. These results have implications for water resource management because of higher tendencies for flooding in the spring and drought in the summer. Copyright © 2011 John Wiley & Sons, Ltd.